Identification of A Novel TGFBI Gene Mutation (p.Serine524Cystine) Associated with Late Onset Recurrent Epithelial Erosions and Bowman Layer Opacities. (1st November 2020) - Chen, Angela C.; Niruthisard, Duangratn; Chung, Doug D.; Chuephanich, Pichaya; Aldave, Anthony J.
ABSTRACT: Background: Most transforming growth factor beta-induced ( TGFBI ) corneal dystrophies are associated with a characteristic phenotype, clinical course, and a conserved mutation in the TGFBI gene. However, we report a novel TGFBI missense mutation associated with a late-onset, variant Bowman layer dystrophy. Methods: Participants underwent slit-lamp examination and multimodal imaging. Polymerase chain reaction amplification and Sanger sequencing were performed on saliva-derived genomic DNA to screen TGFBI exons 4 and 12 as well as COL17A1 exon 46. PolyPhen-2 and SIFT were used to predict the functional impact of any identified variants. Results: A 56-year-old Thai woman reported a four-year history of decreased vision and intermittent eye irritation, suggestive of recurrent epithelial erosions, in both eyes. Slit-lamp exam revealed bilateral, irregular, limbal-sparing Bowman layer opacities, which were also noted on anterior segment optical coherence tomography. Phototherapeutic keratectomy was performed in the right eye, improving the best-corrected visual acuity from 20/50 to 20/30. Sequencing of the TGFBI gene revealed a novel heterozygous, missense mutation in exon 12 (c.1571 C > G; p.Ser524Cys), which was present in an affected son and absent in an unaffected son, and was predicted to be damaging by PolyPhen-2 and SIFT. The patient was diagnosed with a variant Bowman layer dystrophy given the late onset of an atypical phenotype and the identification of a novel TGFBI mutation. Conclusions: A novel TGFBI missense mutation is associated with a late-onset Bowman layer dystrophy. Given the atypical clinical appearance and course, molecular genetic analysis was utilized to establish a definitive diagnosis.